Religiosity, Sexual Attitudes, and Public Perceptions of Sex Work: Evidence of a Mediating Relationship from Italy - Johansson, Isabelle; Hansen, Michael A. (Springer, 2025)
Introduction
This study investigates the relationship between religiosity, general sexual attitudes, and public perceptions of sex work in Italy, a country where religious traditions play a significant role in shaping societal values. We aim to understand how various aspects of religiosity, such as the importance of God, religious service attendance, and prayer frequency, influence attitudes toward the acceptability of sex work.
Methods
We use data from the Wave 5 European Values Study (EVS), a large-scale, cross-national survey that provides insights into individuals’ values and attitudes across Europe. The study focuses on Italy and Italian respondents, examining their views on sex work. Multiple regression models were employed to assess the impact of general sexual attitudes and religiosity on the acceptability of sex work. Mediation analysis was conducted to explore the indirect effects of religiosity through broader sexual norms.
Results
The analysis reveals that general attitudes toward non-committal sexual behavior are the strongest predictors of the acceptability of sex work. While religiosity also influences attitudes, its effect is largely mediated by general beliefs about sexual behavior. The results demonstrate that religiosity has a limited direct impact on attitudes toward sex work in contemporary Italy.
Conclusions
Religiosity, though traditionally a strong influence, now plays an indirect role in shaping views on sex work, mediated by broader societal norms about sexual behavior. These general sexual attitudes are far more significant in determining public perceptions of sex work. This study contributes to the literature by showing that in a highly religious context like Italy, religiosity influences attitudes indirectly through broader sexual norms rather than directly.
Policy Implications
Rather than engaging in morality-based debates linked to religion, advocates and organizations seeking policies that support sex workers may be more effective by emphasizing the normalization of diverse sexual behaviors and shifting broader sexual norms.